Numerical analysis on motion of microparticles passing through straight and tortuous fibrous layers. (14th April 2021) - Otomo, Ryoko; Mori, Kazuki
Abstract: The behavior of microparticle assemblage moving through the saturated pores in a fibrous layer has been investigated numerically. We adopted a particle model to express the straight and tortuous fibrous layers and calculated the velocities of individual microparticles using the Stokesian dynamics approach assuming the Stokes flow. The simulation results showed that the particles spread as they moved through the layer. This is interpreted as hydrodynamic diffusion caused by the hydrodynamic interaction dominant in the Stokes flow. More pronounced diffusion was observed in the tortuous fibrous layer than in the straight one. It was found that the velocity of each particle deviated more from the ensemble average velocity of the assemblage in the tortuous fibrous layer. It was also observed that the tortuous fibrous layers exhibited greater variation in the size of the pores where particles passed. Our results quantitatively indicated that the tortuous fibrous layer consisted of a wide variety of pore sizes, which affects the velocity of the particles passing through it. Consequently, the difference in each particle velocity causes the hydrodynamic diffusion. It was also revealed that the subtle difference in the fiber shape substantially influences the hydrodynamic behavior of the particles moving inside.